Study of the colombian normative framework for horses as blood traction vehicles (2018)
This research aimed at analyzing in detail the Colombian regulations concerning the use of horses as blood traction vehicles, and particularly, their development in the municipality of Florencia, Department of Caquetá. It is clear that a legal framework exist, however, its application is rare or sometimes null, thus perpetuating the impunity of animal abuse crimes, and the lack of effectiveness in terms of social and cultural transformation. The main difficulties found were the lack of both knowledge and effective management of the normative guidelines, and the scarce communication between the entities responsible for compliance, incurring in apparent malfeasance by omission and frank violation of the constitutional principle of administrative coordination.